PENGARUH ALIRAN KAS, PERBEDAAN ANTARA LABA AKUNTANSI DENGAN LABA FISKAL, HUTANG TERHADAP PERSISTENSI LABA PADA PERUSAHAAN JASA INVESTASI - Darmansyah, - (E-Journal Widya Ekonomika, 2018)
Earnings quality is something that is a central and important in the world of accounting, as based on the earnings quality of the accounting profession is at stake. The quality of a company's profits are often associated with the persistence of earnings, due to the persistence of earnings is a relevant component of the qualitative characteristics of the predictive value of the company. This study aims to determine how much influence the effect of cash flow, the difference between accounting income with taxable income and debt to earnings persistence on Investment Services Company listed on the Indonesia Stock Exchange (BEI) either partially or simultaneously. The method used included into the category of quantitative rrelation method. These results indicate that the variable cash flows, the difference between accounting income with taxable income, debt and simultaneously influence the persistence of earnings. While partially variable cash flow significant effect on earnings persistence, variable differences between accounting income to taxable income does not significantly influence the persistence of earnings, and debt to variable significant effect on earnings persistence.